2020
DOI: 10.3389/fvets.2020.00313
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Types of Training Aids Used for Canine Detection Training

Abstract: The canine detection community is a diverse one, ranging from scientific fields such as behavior, genetics, veterinary medicine, chemistry, and biology to applications in law enforcement, military, medicine, and agricultural/environmental detection. This diversity has allowed for a flourishing and innovative community, yet it has also led to little acceptance and agreement on terminology. This is especially true when discussing the variety of training aids used in olfactory-based exercises. In general, authent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Generally, we found that most cases where WDD did not perform better indicated problems in training (37 cases), an issue also highlighted for bird dogs (Gutzwiller, 1990) and scat detection dogs (MacKay et al., 2008). Importantly, good training includes the selection of proper training samples (DeMatteo et al., 2019; Simon et al., 2020) as well as handler abilities (DeMatteo et al., 2019). Issues with the target density (26 cases), study design (21 cases), the target species (20 cases), season‐ and weather‐dependent detectability (14 cases) or an unsuitable area or habitat (13 cases) followed this (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, we found that most cases where WDD did not perform better indicated problems in training (37 cases), an issue also highlighted for bird dogs (Gutzwiller, 1990) and scat detection dogs (MacKay et al., 2008). Importantly, good training includes the selection of proper training samples (DeMatteo et al., 2019; Simon et al., 2020) as well as handler abilities (DeMatteo et al., 2019). Issues with the target density (26 cases), study design (21 cases), the target species (20 cases), season‐ and weather‐dependent detectability (14 cases) or an unsuitable area or habitat (13 cases) followed this (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Several tools have been used as odor adsorbents and transmitters, and as training aids for canine detection training [ 39 ]. Recently, more canine training aids were studied, such as odor capture-and-release materials for explosive odorants and ovarian cancer cell lines for ovarian cancer detection [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, complex targets remain difficult to identify with a unique odor “fingerprint” and they are dynamic samples that can change over time ( 18 ). Therefore, selection of an easily reproducible primary odor target for use as a pseudo-training aid, which does not use the original true material for its production, presents a challenge and may be limited in operational relevance ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with a polymer-based odor capture and release (POCR) training aid demonstrated its capability of presenting qualitatively the same target-based odor profile for explosives such as triacetone triperoxide (TATP), for use in detection canine training ( 20 22 ). This aid represents a non-pseudo alternative that uses the true material in its manufacture directed toward ad/bsorption of the full target odor profile ( 19 ) while eliminating the associated risks and hazardous of handling and use. This technology uses a polymer-based material to safety capture the odor profile of a target of interest, which holds application toward biological targets with complex odor signatures.…”
Section: Introductionmentioning
confidence: 99%